Effect of reduced doses of a post-emergence herbicide to control grass and broad-leaved weeds in no-till wheat under Mediterranean conditions - Barros, José (2007)
A study was carried out over two years (2004/2005 and 2005/2006) on a private farm in the Alentejo region (Évora), in the South of Portugal where rainfed wheat is sown at the start of the winter rainfall season. The wheat crop was established using no-till as this technology provides the necessary machine bearing capacity of the soil to assure the post-emergence application of herbicides at different weed development stages. Mesosulfuron-methyl (3%) and iodosulfuron-methyl-sodium (0.6%) and mefenpyr-diethyl (9%) were used at three doses and two dates with three different application volumes. The results of this study indicate that using lower doses than recommended (0.4 kg ha−1) this herbicide controls the annual grass weeds (Avena sterilis L. and Lolium rigidum G.) better than some broad-leaved weeds. For all doses and volume combinations, the application at the first weed development stage (beginning of tillering for grass weeds and 3–4 pairs of leaves for broad-leaved weeds) provided higher grain yields. The lower efficiency of control of more developed grass and broad-leaved weeds and a longer period of competition between crop and weeds for the second application date (complete tillering for grass weeds and 5–6 pairs of leaves for broad-leaved weeds) were responsible for the significantly lower crop yields for this application date. Within each application date no significant differences were obtained between all dose/volume combinations, indicating that the reduction of dose is possible. At the later application date, the lower herbicide dose seems to require a lower application volume to provide maximum grain yield.